Application of Aesthetic Photography Techniques on Male Faces - Muhammad Ardiansyah; Bambam Julianto (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
This research focuses on evaluating the utilization of aesthetic photography techniques on male faces through a qualitative approach and the adoption of the Multimedia Development Life Cycle (MDLC) method. Subsequently, the researcher engages in the development and testing phases by capturing male faces using specific photography techniques. The MDLC method is implemented through stages like concept, design, material collection, assembly, testing, and distribution. The research findings highlight the importance of selecting appropriate angles, lighting, and coloring in applying aesthetic photography techniques to male faces. Conclusions are drawn based on respondents' evaluations of the photographic results.